An update on Aenocyon dirus in the interior of North America: new records, radiocarbon dates, ZooMS spectra, and isotopic data for an iconic late Pleistocene carnivore - Hill, Matthew G.; Widga, Christopher C.; Surovell, Todd A.; Wilson, Kurt M.; Allaun, Sarah A.; Litynski, McKenna L.; Titcomb, Jason (PeerJ, 2025)
Aenocyon dirus played a crucial role as a predator in late Quaternary megafaunal communities throughout southern North America. This article presents two new occurrences of the species from southwest Iowa on the eastern Great Plains, updates the Peccary Cave record in the southern Ozark Highlands, and amends the fossil record of the species. In southern North America, there are 166 occurrences of A. dirus, spanning Marine Isotope Stage (MIS) 2-19, with at least two-thirds (n = 112) of the occurrences dating to MIS 2-3 (11,600–57,000 cal B.P.). A. dirus fossils are found across this region, with notable concentrations in California, Florida, the Ozark Highlands, and broadly across the southern Great Plains. Consideration of Canis specimens from the lead region (covering contiguous parts of Illinois, Wisconsin, and Iowa) previously identified as Canis mississippiensis (and sometimes synonymized with A. dirus or C. lupus) reveals they are actually C. lupus. The terminal extinction of A. dirus occurred sometime after 12,800 cal B.P. The Iowa finds, consisting of a radius and a partial cranium, are the first records for the state. Zooarchaeology by mass spectrometry confirms these records, as well as the Peccary Cave record, are A. dirus, as opposed to C. lupus. The Iowa specimens are directly dated to 29,040–28,410 cal B.P. and 14,325–14,075 cal B.P., while Peccary Cave is dated to 25,350–21,405 cal B.P. These results place A. dirus in the interior of southern North America before, during, and after the Last Glacial Maximum (26,500–19,000 cal B.P.). Stable nitrogen isotope (δ15N) values of bone collagen from the younger of the two Iowa records suggest this individual did not regularly compete for prey with Smilodon fatalis during the Bølling-Allerød Chronozone (14,640–12,850 cal B.P.). To the south, at Peccary Cave, considerations of prey size, prey abundance, and isotopic data strongly suggest Platygonus compressus was the focal prey species.
Keywords: Quaternary; Pleistocene; Canidae; Dire wolf; Vertebrate taphonomy; Paleoecology; Extinction